2021
DOI: 10.1038/s41598-021-91195-2
|View full text |Cite
|
Sign up to set email alerts
|

Lung microbiome alterations in NSCLC patients

Abstract: Lung is colonized by a diverse array of microbes and the lung microbiota is profoundly involved in the development of respiratory diseases. There is little knowledge about the role of lung microbiota dysbiosis in lung cancer. In this study, we performed metagenomic sequencing on bronchoalveolar lavage (BAL) from two different sampling methods in non-small cell lung cancer (NSCLC) patients and non-cancer controls. We found the obvious variation between bronchoscopy samples and lobectomy samples. Oral taxa can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 42 publications
3
29
1
1
Order By: Relevance
“…Both of them are Gram-negative, facultatively anaerobic coccobacillus and have been previously identified in lung cancer patients with various degrees of lung inflammation ( 24 ). The whole of Faecalibacterium ASVs were identified as Faecalibacterium prausnitzii , which was highly abundant in the human gut microbiota in healthy individuals and can regulate the expression of proinflammatory and anti-inflammatory cytokines in the gut-lung axis through the secretion of extracellular alveoli ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both of them are Gram-negative, facultatively anaerobic coccobacillus and have been previously identified in lung cancer patients with various degrees of lung inflammation ( 24 ). The whole of Faecalibacterium ASVs were identified as Faecalibacterium prausnitzii , which was highly abundant in the human gut microbiota in healthy individuals and can regulate the expression of proinflammatory and anti-inflammatory cytokines in the gut-lung axis through the secretion of extracellular alveoli ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, studies have confirmed that the lung microbiome (LM) differs among clinicopathology types ( 1 ), and lung microbial flora may impact the development of NSCLC ( 2 ). However, the detailed role and characteristics of LM in NSCLC are not fully known ( 3 ). In addition, existing studies commonly presented the comorbidity of respiratory infection and NSCLC onset.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, existing studies mainly focus on the LC tissues. However, LM composition can vary among lung segments ( 3 ). Therefore, it is more valuable to combine multiple levels of detection, e.g., tumor tissues, blood plasma, and bronchoalveolar fluid (BALF), but not single tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that certain microbes are associated with cancer progression is confirmed by the observation that species in NSCLC are associated with the genetic profile of neoplastic cells. The main attention has been devoted to the correlation of EGFR status and lung microbiome, and experimental reports already suggested that in bronchoscopy-obtained NSCLC samples, the detection of EGFR-mutant cells has been correlated with the abundance of rare species, such as Rhizopus oryzae, Natronolimnobius innermongolicus, Staphylococcus sciuri [18]. The genus Parvimonas has been documented to be significantly enriched in EGFR-mutant adenocarcinomas as well [53].…”
Section: Genetic Signatures On Microbiota and Effect Of Microbiota On...mentioning
confidence: 99%
“…It has been already demonstrated that the microbiome found in NSCLC patients is similar in composition to that of healthy subjects even though with a higher grade of dysbiosis due to the rare species, e.g., Lactobacillus rossiae, Bacteroides pheteryogenes, Paenibacillus odorifer, Pseudomonas entomophila, Magnetospirillum gryphiswaldense, fungus Chaetomium globosum [18]. In healthy subjects, the microbiota composition is modulated by the effects of different conditions, which include aspiration of oral secretions, the interaction with the host immune system [19] and the constant interaction between pulmonary and distal microbiota, mainly that in the gut.…”
Section: Introductionmentioning
confidence: 99%